St. Hildegard of Bingen’s Integral Ecology: Insights from Her Trinitarian Theology - Mello, Bruno (Theology and science, 2025)
The writings of St. Hildegard of Bingen (1098–1171), the twelfth century abbess, mystic, and polymath, have become important touchstones in the emergent field of ecotheology. In search of a model of integral ecology, this paper will examine Hildegard’s ecological worldview by way of her medical writings and her novel concept of viriditas, then propose to approach Hildegard’s ecology by way of her theology of the Trinity. This exploration will affirm as indispensable certain notes of Hildegard’s ecotheological vision, namely, the centrality of the Incarnation, the invitation to contemplation and paradox, and an emphasis on upholding orthodox Catholic doctrine.